Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.ydbio.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog receptor function during craniofacial development

Abstract: The Hedgehog signalling pathway plays a fundamental role in orchestrating normal craniofacial development in vertebrates. In particular, Sonic hedgehog (Shh) is produced in three key domains during the early formation of the head; neuroectoderm of the ventral forebrain, facial ectoderm and the pharyngeal endoderm; with signal transduction evident in both ectodermal and mesenchymal tissue compartments. Shh signalling from the prechordal plate and ventral midline of the diencephalon is required for appropriate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 224 publications
1
104
0
5
Order By: Relevance
“…Specifically, secretion of SHH ligand from the ectoderm activates pathway activity in the adjacent cranial neural crest-derived mesenchyme (Marcucio et al, 2005;Hu and Marcucio, 2009;Hu et al, 2015;Xavier et al, 2016). Demonstrating clinical relevance, we have shown that transient in utero exposure to the Shh pathway inhibitor cyclopamine causes lateral clefts of the lip that typically extend into the primary and secondary palate, and that this model recapitulates human non-syndromic cleft lip with or without cleft palate (CL/P) (Lipinski et al, 2008b(Lipinski et al, , 2010(Lipinski et al, , 2014.…”
Section: Introductionmentioning
confidence: 58%
“…Specifically, secretion of SHH ligand from the ectoderm activates pathway activity in the adjacent cranial neural crest-derived mesenchyme (Marcucio et al, 2005;Hu and Marcucio, 2009;Hu et al, 2015;Xavier et al, 2016). Demonstrating clinical relevance, we have shown that transient in utero exposure to the Shh pathway inhibitor cyclopamine causes lateral clefts of the lip that typically extend into the primary and secondary palate, and that this model recapitulates human non-syndromic cleft lip with or without cleft palate (CL/P) (Lipinski et al, 2008b(Lipinski et al, , 2010(Lipinski et al, , 2014.…”
Section: Introductionmentioning
confidence: 58%
“…Shh signaling is an important component of proper craniofacial development [13,29]. Furthermore, Shh signaling is mediated by post translational cholesterol modifications [30] and mutations in the proteins that facilitate these modifications have been associated with craniofacial abnormalities [3133].…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in either the murine or telost Disp1 genes result in craniofacial abnormalities [31,33]. Moreover, human mutations in the Shh pathway cause overlapping phenotypes when compared with mutations that interfere with the cholesterol synthesis pathway [29,52]. In vitro experiments also suggest that deficiencies in the cholesterol synthesis pathway reduce Shh signaling by interfering with smoothened activation, but very few studies have linked these two pathways in vivo [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the developmental specification of the cell fate, Shh signaling plays crucial roles in early patterning of the embryonic brain, notably to regulate polarity of the central nervous system (CNS) [6] as well as to guide the ventral patterning in the spinal cord [7]. These features are important for craniofacial development because disruption of Shh signaling pathway may cause craniofacial neural crest cell death, thereby resulting in craniofacial anomalies in both vertebrate models and human populations [8,9]. During early stages of head formation, Shh is produced in three key domains, namely neuroectoderm of the ventral forebrain, facial ectoderm, and the pharyngeal endoderm [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These features are important for craniofacial development because disruption of Shh signaling pathway may cause craniofacial neural crest cell death, thereby resulting in craniofacial anomalies in both vertebrate models and human populations [8,9]. During early stages of head formation, Shh is produced in three key domains, namely neuroectoderm of the ventral forebrain, facial ectoderm, and the pharyngeal endoderm [8,9]. Shh signaling is critical for orchestrating the fundamental organization of the craniofacial region [10,11].…”
Section: Introductionmentioning
confidence: 99%